Connectivity of Pathology: The Olfactory System as a Model for Network-Driven Mechanisms of Alzheimer’s Disease Pathogenesis - Franks, Katherine H.; Chuah, Meng Inn; King, Anna E.; Vickers, James C. (Frontiers in Aging Neuroscience, 2015)
The pathogenesis of Alzheimer’s disease has been postulated to preferentially impact specific neural networks in the brain. The olfactory system is a well-defined network that has been implicated in early stages of the disease, marked by impairment in olfaction as well as the presence of pathological hallmarks of the disease, even before clinical presentation. Discovering the cellular mechanisms involved in the connectivity of pathology will provide insight into potential targets for treatment. We review evidence from animal studies on sensory alteration through denervation or enrichment, which supports the notion of using the olfactory system to investigate the implications of connectivity and activity in the spread of pathology in Alzheimer’s disease.